Tracheal Trifurcation Associated With Esophageal Atresia - Sarin, Yogesh Kumar (EL-MED-Pub, 2010)
We report a newborn with esophageal atresia (EA) in whom right tracheal bronchus (TB) and a tracheal diverticulum were identified intra-operatively. The right TB was further confirmed on MRI scan performed post-operatively. Such a tracheal trifurcation associated with EA has not been reported hitherto from Indian subcontinent.